Re-examining poikilocytosis in goats: prevalence, type and association with age and disease - Vasilatis, Demitria M.; Christopher, Mary M. (Frontiers in Veterinary Science, 2023)
Domestic goats (Capra aegagrus hircus) are a food, fiber and companion animal. Abnormal erythrocyte shapes (poikilocytes) are considered normal in young goats, but their association with disease is not well described. Likewise, there is little information on the significance of poikilocytosis in adult goats. The objective of this study was to investigate the prevalence, severity and type of poikilocytosis in young and adult goats and its association with age, sex, breed, laboratory results, and underlying disease. We retrospectively examined clinical and laboratory data from 1254 goats presented at the University of California-Davis Veterinary Medical Teaching Hospital from 1997 to 2019. We analyzed 313 blood smears from goats with moderate or marked (MOD-MKD) poikilocytosis on initial blood smear evaluation. Number and type of poikilocytes per 1000 red blood cells (RBCs) were enumerated. Laboratory values and primary disease categories were compared with the severity and type of poikilocytosis. Kids (<6 mos) and juveniles (>6 mos to <1 year) had a higher prevalence of MOD-MKD poikilocytosis (95/210, 45.2% kids; 27/59, 45.8% juveniles) than adult goats (≥1 year; 190/982, 19.3%) (P < .001). Kids had a higher percentage of elliptocytes, dacryocytes, and schistocytes and a lower percentage of polygonal and spiculated RBCs than juvenile and adult goats (P < .001). Of goats with MOD-MKD (vs NONE-SLIGHT) poikilocytosis, kids had lower HGB and MCH, and higher RDW (P ≤ .02); juveniles and adult goats had lower HCT, MCV, MCH, and albumin concentration (P ≤ .01), and all age groups had lower total CO2 concentration and higher PLT counts (P < .03). Adult goats with MOD-MKD poikilocytosis also had higher BUN:Cr ratios (P = .005). Gastrointestinal parasitism, Johne's disease, diarrhea/enteritis, lice, hepatic disease and renal disease (but not urolithiasis) were significantly associated with MOD-MKD poikilocytosis (P < .001). Goats with hepatic and renal disease had a higher prevalence and percentage of spiculated cells (P = .001). Goats with Johne's disease had a higher prevalence of polygonal cells (93.3%) and dacryocytes (66.7%) than other diseases and elliptocytes predominated in a higher proportion (36.0%) of adult goats with GI parasitism vs other diseases (P < .05).